Quality control for retinal OCT in multiple sclerosis: validation of the OSCAR-IB criteria. (February 2015) - Schippling, S; Balk, LJ; Costello, F; Albrecht, P; Balcer, L; Calabresi, PA; Frederiksen, JL; Frohman, E; Green, AJ; Klistorner, A; Outteryck, O; Paul, F; et al.
Background: Retinal optical coherence tomography (OCT) permits quantification of retinal layer atrophy relevant to assessment of neurodegeneration in multiple sclerosis (MS). Measurement artefacts may limit the use of OCT to MS research. Objective: An expert task force convened with the aim to provide guidance on the use of validated quality control (QC) criteria for the use of OCT in MS research and clinical trials. Methods: A prospective multi-centre ( n = 13) study. Peripapillary ring scan QC rating of an OCT training set ( n = 50) was followed by a test set ( n = 50). Inter-rater agreement was calculated using kappa statistics. Results were discussed at a round table after the assessment had taken place. Results: The inter-rater QC agreement was substantial (kappa = 0.7). Disagreement was found highest for judging signal strength (kappa = 0.40). Future steps to resolve these issues were discussed. Conclusion: Substantial agreement for QC assessment was achieved with aid of the OSCAR-IB criteria. The task force has developed a website for free online training and QC certification. The criteria may prove useful for future research and trials in MS using OCT as a secondary outcome measure in a multi-centre setting.